Paroxysmal Discharges in Tissue Slices From Pediatric Epilepsy Surgery Patients: Critical Role of GABAB Receptors in the Generation of Ictal Activity - Levinson, Simon; Tran, Conny H.; Barry, Joshua; Viker, Brett; Levine, Michael S.; Vinters, Harry V.; Mathern, Gary W.; Cepeda, Carlos (Frontiers in Cellular Neuroscience, 2020)
In the present study, we characterized the effects of bath application of the proconvulsant drug 4-Aminopyridine (4-AP) alone or in combination with GABAA and/or GABAB receptor antagonists, in cortical dysplasia (CD type I and CD type IIa/b), tuberous sclerosis complex (TSC) and non-CD cortical tissue samples from pediatric epilepsy surgery patients. Whole-cell patch clamp recordings in current and voltage clamp modes were obtained from cortical pyramidal neurons (CPNs), interneurons, and balloon/giant cells. In pyramidal neurons, bath application of 4-AP produced an increase in spontaneous synaptic activity as well as rhythmic membrane oscillations. In current clamp mode, these oscillations were generally depolarizing or biphasic and were accompanied by increased membrane conductance. In interneurons, membrane oscillations were consistently depolarizing and accompanied by bursts of action potentials. In a subset of balloon/giant cells from CD type IIb and TSC cases respectively, 4-AP induced very low-amplitude, slow membrane oscillations that echoed the rhythmic oscillations from pyramidal neurons and interneurons. Bicuculline reduced the amplitude of membrane oscillations induced by 4-AP, indicating they were mediated principally by GABAA receptors. 4-AP alone or in combination with bicuculline increased cortical excitability but did not induce seizure-like discharges. Ictal activity was observed in pyramidal neurons and interneurons from CD and tuberous sclerosis complex cases only when phaclofen, a GABAB receptor antagonist, was added to the 4-AP and bicuculline solution. These results emphasize the critical and permissive role of GABAB receptors in the transition to an ictal state in pediatric CD tissue and highlight the importance of these receptors as a potential therapeutic target in pediatric epilepsy.